Efficacy of red ointment in wound cavity repair following non-puerperal mastitis debridement - Jiamei Feng; Zheng Chen; Jiaye Sun; Shijun Shao; Lu Xie; Wenchao Qu; Qingqian Gao; Xueqing Wu; Hua Wan (Hereditas)
Abstract Background The objective of this study is to evaluate the efficacy of red ointment, a widely used topical agent in traditional Chinese medicine, in promoting wound cavity repair following debridement for non-puerperal mastitis (NPM). Methods A prospective, randomized controlled trial was conducted, including 88 patients diagnosed with NPM. Patients were randomly assigned to either the treatment group or the control group. All patients underwent debridement during the acute inflammatory phase. Postoperatively, the treatment group received daily dressing changes using sterile gauze strips infused with red ointment, whereas the control group received sterile gauze strips soaked in rivanol. The effectiveness of treatment was assessed after two weeks by evaluating the total effective rate, wound cavity score, symptom and sign score, laboratory parameters, and adverse events. Results In the intention to treat analysis, the total effective rate was 90.9% in the red ointment group, which was higher than the 86.4% observed in the rivanol group. In the per protocol analysis, the total effective rate was 97.6% in the red ointment group, exceeding the 92.7% in the rivanol group. Compared with rivanol-treated gauze strips, the use of red ointment gauze strips resulted in a significantly greater reduction in wound cavity volume (p < 0.05), improved local breast symptoms (p < 0.05), and a lower wound cavity score (p < 0.001). Granulation tissue in the red ointment group exhibited a significantly fresher color compared to the rivanol group (p < 0.05). No significant differences were observed between the two groups regarding adverse effects on hepatic and renal function following treatment. Conclusion The use of red ointment gauze strips for wound cavity filling following NPM debridement demonstrated favorable clinical efficacy and safety, providing a viable option for postoperative drainage management.